Nanaphora rufozonata Laseron 1958 - Bakker, Piet A. J.; Albano, Paolo G. (Zenodo, 2022)
Nanaphora rufozonata Laseron, 1958 Nanaphora rufozonata Laseron, 1958: 615, fig. 139–140. Type locality. Australia, Barrier Reef off Cairns. Type material. AMS C.46015, holotype. Distribution. Australia (Laseron 1958). ( † ) Triforis rufula R.B. Watson, 1886 Triforis rufula R.B. Watson, 1886: 566, pl. 42, fig. 2. Mastonia rufula (R.B. Watson, 1886) — Hervier 1899: 310. Triphora rufula R.B. Watson, 1886 — Hedley 1907: 481. Notosinister rufula (R.B. Watson, 1886) — Laseron 1958: 632, fig. 196–197. Notosinister rufulus (R.B. Watson, 1886) — Kosuge 1963a: 241, pl. 14, fig. 8. Triphora ( Mastonia ) rufula R.B. Watson, 1886 —Selli 1974: 333, pl. 19, fig. 15a, 15b. Monophorus rufulus (R.B. Watson, 1886) — Okutani 2000: 305, pl. 151, fig. 19. Type locality. Australia, North-East Australia, Cape York, Off Wednesday Island, 10°30’S, 142°18’E, 8 fathoms deep (15 m), coral mud. Type material. NHMUK 1887.2.9.1768, lectotype. NHMUK 1887.2.9.1769–1887.2.9.1771, paralectotypes. Distribution. Australia (Watson 1886; Tryon 1887; Paetel 1888; Hedley 1907; Laseron 1958; Kosuge 1963a; Selli 1974; Albano et al. 2019), Eritrea (Selli 1974), French Polynesia (Boutet et al. 2020), Japan (Kosuge 1963a; Higo et al. 1999; Okutani 2000; Okutani 2017), New Caledonia (Hervier 1899), Philippines (Higo et al. 1999). Geological age. Quaternary (Selli 1974). Remarks. Lectotype designation by Albano et al. (2019). Published as part of Bakker, Piet A. J. & Albano, Paolo G., 2022, Nomenclator, geographic and stratigraphic distribution of the family Triphoridae (Mollusca: Gastropoda), pp. 1-216 in Zootaxa 5088 (1) on page 154, DOI:10.11646/zootaxa.5088.1.1, http://zenodo.org/record/5836536